Indenture as a Commitment Device in Self-Enforced Contracts: An Experimental Test - Alexander S. Kritikos; Jonathan H. W. Tan (European University Viadrina, Department of Business Administration and Economics, 2005)
How can a principal (an agent) ensure that an agent (a principal) will work (pay up), if payment (work) precedes work (payment)? When a banknote is torn in two, each part is by itself worthless. A principal can pre-commit to payment-on-delivery, by tearing a banknote and giving the agent the first half as "prepayment"; the agent receives the completing half upon delivery of the service. This contract design is known as "indenture". It is self-enforcing and incentive-compatible. This paper experimentally tests the efficacy of the "indenture game" and its implications for cooperation in oneshot environments. We find that cooperation rates are high and stable over time. Its efficacy is moderated by expected losses due to the existence of uncooperative types.
Keywords: C91; J41; D64; 330; Cooperation; Experiment; Contracts; Indenture; Reciprocity; Agency Theory; Spieltheorie; Anreizvertrag; Experiment; Theorie